Dongeng “Dunia Mangrove” Berbasis Augmented Reality untuk Melestarikan Objek Wisata Pesisir bagi Anak Usia Dini - Eriqa Pratiwi; Tarich Yuandana; Nosia Khosiyana (PG-PAUD Trunojoyo, 2023)
The development of the world of early childhood education is currently increasing rapidly marked by the use of learning media that prioritizes technology such as fairy tales based on augmented reality. However, the use of technology-based learning media such as fairy tales based on augmented reality is still limited. This is based on the results of observations at the age of 4-6 years who live around the Labuhan mangrove education park. The fairy tale "Mangrove World" was developed using Augmented Reality-based technological developments which aim to teach about the phenomena of flora and fauna life and how to preserve mangroves in the environment where children live. This study used the ADDIE development model with two analytical techniques, namely descriptive qualitative and descriptive statistics conducted at two kindergarten institutions in Sepuluh District, Bangkalan Regency. Based on the analysis of the feasibility test results, it was stated that an AR-based fairy tale with the title "Mangrove World" was declared feasible to be used as a learning medium and effective for increasing children's understanding of flora and fauna, benefits and ways to preserve mangrove forests as coastal tourism objects. The contribution of the development of the AR-based fairy tale "World of Mangrove" can be used as a fun medium to provide understanding to children to preserve coastal tourism objects.